METHOD TO IDENTIFY THE FACIES ASSOCIATION ARCHITECHTURE BASED ON CORE ANALYSIS - Ganjar Gani, Reza Mohammad; Firmansyah, Yusi; Nurdeani, Rifky (Journal of Geological Sciences and Applied Geology, 2017)
Rock is a very important in knowing the geological processes that developed in the past and present. The geological processes recorded in the core rock or often known as the core. Core is a rock of subsurface drilling. From the rock core can be known the characteristics of rocks ranging from megascopic and microscopic characteristics. The results of megascopic and microscopic analysis will be known facies, deposit environments, facies associations and architecture. The data contained 3 rocks that have been in the description, after the analysis there are 3 facies including the foraminifera limestone, sandstone foraminifera and claystone foraminifera. The foraminifera limestone is deposited on the Patch Reef Interior Platform environment, the foraminifera sandstones are deposited on the Restricted Interior's platform environment and the foraminifera claystone is deposited on the Open Marine Interior Platform environment. All three facies are integrated into the facies association Restricted - Open Marine Platform.Keywords : Core, Facies, Facies Association